2011
DOI: 10.1111/j.1445-6664.2011.00402.x
|View full text |Cite
|
Sign up to set email alerts
|

Confirmed resistance to aryloxyphenoxypropionate herbicides in Phalaris minor populations in Iran

Abstract: Phalaris minor (littleseed canary grass) is a major weed in wheat fields in some parts of Iran. Diclofop-methyl, fenoxaprop-P-ethyl, and clodinafop-propargyl are three acetyl coenzyme A carboxylase (ACCase)-inhibiting herbicides that are commonly used to control this grass in wheat fields.Thirty-four P. minor populations with suspected resistance to ACCase-inhibiting herbicides were sampled from wheat fields in the provinces of Fars and Golestan in Iran.The dose-response assays that were conducted under contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 26 publications
2
26
0
Order By: Relevance
“…A similar trend has been previously reported in the case of the plant species treated with aryloxyphenoxy propionate Volume 12, No 2, March-April 2018; http://www.ijt.ir group of herbicides such as Quizalofop-p-ethyl and fluazifop-p-buthyl [10,11,30]. This group of herbicides can indirectly disrupt fatty acid biosynthesis via the inhibition of ACCase [11,31,32]. Therefore, GS, which belongs to this group, can inhibit the formation of thylakoids membranes and finally reduce the pigments content, thereby causing chlorosis.…”
Section: Discussionsupporting
confidence: 61%
“…A similar trend has been previously reported in the case of the plant species treated with aryloxyphenoxy propionate Volume 12, No 2, March-April 2018; http://www.ijt.ir group of herbicides such as Quizalofop-p-ethyl and fluazifop-p-buthyl [10,11,30]. This group of herbicides can indirectly disrupt fatty acid biosynthesis via the inhibition of ACCase [11,31,32]. Therefore, GS, which belongs to this group, can inhibit the formation of thylakoids membranes and finally reduce the pigments content, thereby causing chlorosis.…”
Section: Discussionsupporting
confidence: 61%
“…Resistance is particularly widespread in L. rigidum throughout the Australian wheat belt, in practically every single cereal farm infested with A. myosuroides in the United Kingdom and in A. fatua in large areas in Western Canada . Other affected grass weed populations described recently include Phalaris minor from India, Greece and Iran, Phalaris paradoxa from Italy and Israel, Sorghum halepense from Greece and the United States, Brachiaria plantaginea from Brazil, Digitaria sanguinalis from France, Apera spica‐venti from Central and Eastern Europe and Alopecurus japonicus and Beckmannia syzigachne from China, along with many other species from various regions as summarised in the International Survey of Herbicide Resistant Weeds website . The areas concerned nevertheless remain an underrepresentation of the real status of resistance to ACCase herbicides as there are some weed species and populations such as Lolium spp., Sclerochloa kengiana and Fimbristilis miliacea from North Africa, China and Vietnam respectively that are not documented but are highly suspected to be affected by resistance.…”
Section: Occurrence Evolution and Spread Of Resistancementioning
confidence: 99%
“…Fields from different locations received different herbicidal and non-herbicidal weed control approaches (Travlos et al, 2011). A difference in resistance level could also be due to different resistance mechanisms (altered target site, enhanced metabolism, existence of modified ACCase, compartmentalization or over-expression of the target protein) present in P. minor biotypes and other weed species (Maneechote et al, 1994;Gherekhloo et al, 2011;Travlos et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Heap (2015) reported that the herbicide selection pressure is continually increasing the resistant biotypes of different weeds. After the first case of P. minor resistance to isoproturon during 1995 in India, P. minor biotypes have developed resistance to ALS-inhibiting herbicide (sulfosulfuron), ACCase-inhibiting herbicides (clodinafop, fenoxaprop and tralkoxydim) and other herbicides with these modes of actions (Chhokar and Malik, 2002;Chhokar and Sharma, 2008;Gherekhloo et al, 2011). Many P. minor biotypes have evolved cross and multiple resistance to herbicides, having different modes of action in different parts of the world (Heap, 2015).…”
Section: Introductionmentioning
confidence: 99%